Preparing teachers for students in juvenile justice settings - Larkin, Douglas B. (Contemporary justice review, 2020)
In the United States, there is an urgent need to ensure that youth held in correctional facilities are provided with high-quality teachers while in the juvenile justice system. Drawing upon the scholarship of educational practices in correctional settings and teacher education, this review presents what is known and what still needs to be learned in order to ensure that youth in the American juvenile justice system receive the free and public education to which they are entitled. Findings from this review indicate that while specialized knowledge, skills, and credentialing in special education, mental health, and cultural competence appear to be essential for teachers in these settings, there is currently very little research on teacher preparation for such populations, and the field would benefit from a sustained program of research on the preparation of teachers for students in juvenile justice settings.